Dissemination of Faith in The Early Muslim Community in The Mecca Period: An Analysis of The Process And its Impact on Islamic Faith Education - Abdurrohim Abdurrohim; Adiyono Adiyono; Makmur Harun (International Journal Ihya' 'Ulum al-Din, 2023)
This article discusses the historical chronicles of Prophet Muhammad SAW and their significance in integrating faith values into Islamic education. The focus of this research is on the historical process that occurred during the period of Mecca, where the foundation of the Islamic faith was laid. This study aims to explore the dissemination process of the Islamic faith during the early Muslim community in Mecca, its significance in integrating faith values in Islamic education, and its implications for the renewal of the curriculum and teaching methods of the Islamic faith in the present time.  This study uses the prophetical-transformative theory proposed by Kuntowijoyo, which emphasizes the integration of modern science with the prophetic ideals of Islam.  The article concludes that the historical chronicles during the time of the Prophet Muhammad saw. are crucial for understanding the foundation of the Islamic faith and its integration into Islamic education. The paradigmatic core values in Islamic faith education emphasize the importance of core values, which should be the basis for religious education. These core values reflect profound principles in Islam and should be an integral part of efforts to reform the Islamic faith learning curriculum. This article recommends the rediscovery of the historical facts of the dissemination of the Islamic faith during the early Muslim community in Mecca as a basis for the renewal of the curriculum and teaching methods of the Islamic faith in the present time.